Analisis Sensitivitas Model Goal Programming Pada Optimasi Produksi Roti Menggunakan Metode Branch and Bound - Ahmad, Rindawati; Katili, Muhammad Rifai; Mahmud, Sri Lestari; Wungguli, Djihad; Nashar, La Ode (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
Sya'qila Bakery is a manufacturing industry that produces bread in five flavor variants. The planning carried out by Sya'qila Bakery in the bread production process is considered suboptimal due to the limitation in the quantity of production for each flavor variant, resulting in occasional shortages of raw materials. Additionally, the order production process requires a long total completion time (makespan), resulting in delays in production completion (meaning tardiness). This research aims to optimize the total completion time, the average lateness, the use of raw materials, and production revenue. In this research, the Goal Programming model is utilized with the Branch and Bound method. The analysis results with the Goal Programming model using the Branch and Bound method obtain an optimal solution, which includes an excess of 36 minutes in total completion time (makespan), an excess of 6 minutes in average lateness (mean tardiness), no excess in the availability of raw materials, and zero sales revenue shortfall. Sensitivity analysis results indicate that bread production at Sya'qila Bakery will remain optimal if changes occur in the production completion time, production delay time, and raw material availability, as long as these changes remain within their tolerance limits.